2021
DOI: 10.3390/ijms22031196
|View full text |Cite
|
Sign up to set email alerts
|

High Potential of Pichia kluyveri and Other Pichia Species in Wine Technology

Abstract: The surfaces of grapes are covered by different yeast species that are important in the first stages of the fermentation process. In recent years, non-Saccharomyces yeasts such as Torulaspora delbrueckii, Lachancea thermotolerans, Metschnikowia pulcherrima, and Pichia kluyveri have become popular with regard to winemaking and improved wine quality. For that reason, several manufacturers started to offer commercially available strains of these non-Saccharomyces species. P. kluyveri stands out, mainly due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 74 publications
2
48
0
Order By: Relevance
“…The following commercial strains of Pichia kluyveri are offered: Viniflora FrootZen (monoculture offered by CHR Hansen, Hørsholm, Denmark) and Trillyeast (in consortium with Kazachastania servazzii, offered by BioEnologia, Oderzo, Italy) (Table 1). Recently, the commercial strain Pichia kluyveri WLP605 (Vintner's Harvest, Yakima, WA, United States) was reported and recommended to confer floral and rose petal aromas [28].…”
Section: Pichia Kluyverimentioning
confidence: 99%
See 1 more Smart Citation
“…The following commercial strains of Pichia kluyveri are offered: Viniflora FrootZen (monoculture offered by CHR Hansen, Hørsholm, Denmark) and Trillyeast (in consortium with Kazachastania servazzii, offered by BioEnologia, Oderzo, Italy) (Table 1). Recently, the commercial strain Pichia kluyveri WLP605 (Vintner's Harvest, Yakima, WA, United States) was reported and recommended to confer floral and rose petal aromas [28].…”
Section: Pichia Kluyverimentioning
confidence: 99%
“…However, the concentration of this acid was not high enough to be detected in the sensory analysis. It was suggested that the synthesis of isovaleric acid can be considered a criterion for the selection of P. kluyveri [28] and that its esterification can produce the ethyl ester of 3-methyl-butanoic acid, which has a pleasant fruity aroma.…”
Section: Pichia Kluyverimentioning
confidence: 99%
“…Using Starmerella bacillaris mixed with S. cerevisiae produced significantly lower levels of acetic acid, ethanol, and ethyl acetate, and higher amounts of glycerol, higher alcohols, and esters [ 13 ]. P. kluyveri improves wine quality parameters such as thiol, fruity ester, and terpene concentrations, mainly in sequential fermentation [ 14 ]. Higher concentration of medium-chain fatty acids was associated with the higher biomass suppression of H. uvarum in co-inoculation with killer S. cerevisiae , which resulted in the increased formation of fruity esters, but effectively restricted the production of ethyl acetate [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pichia kluyveri , another popular non- Saccharomyces yeast, is well known for its characteristics of low ethanol production but high acetate esters (e.g. 2-phenylethyl acetate) production ( Vicente et al, 2021 ). Previous studies have demonstrated that P. kluyveri improved the aroma quality of various types of alcoholic beverages including fruits media (e.g.…”
Section: Introductionmentioning
confidence: 99%